الاغتراب نسقاً للرّفض من خلال رواية "ثورة الملائكة؛ حكاية القطّة التي أكلت أطفالها" لأحمد زغب. - السعيد, قبنة (جامعة الوادي - University of Eloued, 2022)
رواية (ثورة الملائكة) –موضوع الدراسة- للكاتب (أحمد زغب) إسقاط واقعي لحالة الاغتراب النسقي التي وجد الشعب الجزائري نفسه مكبّلا بها بعد الاستقلال، ممّا حرمه من فرصة إقلاع حضاري يليق بتضحيات أجيالٍ طويلةٍ من الشهداء. ومن أجل الكشف عن مضمرات الخطاب في موضوع الاغتراب نسقا للرفض في هذه الرواية قمنا بتحليل تلك الرموز والدّلالات التي وظفها الكاتب فيها، مستأنسين في ذات الوقت بآراء ومقاربات النقد الثقافي. The novel of (the Revolution of Angels) – the subject of study - by the writer (Ahmed Zeghab) is a realistic projection of the alienation format's state that the Algerian people found themselves shackled to after the independence, which deprived them of the opportunity to a civilizational rise worthy of the sacrifices of martyrs' long generations . In order to reveal the connotations of the discourse in the subject of the alienation as a rejection format in this novel, we have analyzed those symbols and indications in which the writer employed. In the same time, we are supported by the views and approaches of cultural criticism.
مقال
Keywords: : نسق، اغتراب، ثقافة، رمز، ثورة; Alienation, Culture, Format, Symbol, Revolution